An Elderly Lady with Fever of Unknown Etiology and Severe Pulmonary Hypertension: Intravascular Lymphoma—An Elusive Diagnosis - Nupur Sinha; Luis Lantigua; Masooma Niazi; Gilda Diaz-Fuentes (Case Reports in Medicine)
Pulmonary hypertension (PH) associated with malignancy, especially adenocarcinoma, is a well-known entity and is included in group V of the WHO classification. Intravascular lymphoma is a rare type of diffuse large B cell lymphoma, characterized by selective intravascular growth of malignant lymphocytes, aggressive behavior, and often a fatal course. Most of the time, diagnosis is postmortem due to the rarity and the protean manifestations of the disease. We present a rare case of an elderly patient presenting with severe pulmonary hypertension, fever of unknown etiology (FUO), and lymphadenopathy. Extensive evaluation searching for the etiology of her FUO and PH was noncontributory. The diagnosis of intravascular lymphoma was finally reached by the performance of a random abdominal fat pad biopsy and the patient was started on immunochemotherapy. She continues the follow up after 6 cycles of R-CHOP with no further febrile episodes and steady improvement in exercise tolerance.